Hs, p regularity theory for a class of nonlocal elliptic equations. (June 2020) - Nowak, Simon
Abstract: In this paper, we study the regularity of weak solutions to a class of nonlocal elliptic equations in Bessel potential spaces H s, p . Our main results can be seen as an extension of the well-known W 1, p regularity theory for local second-order elliptic equations in divergence form to the nonlocal setting.